2017
DOI: 10.3892/ol.2017.7247
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of sarcoidosis and metastatic lesions: A diagnostic and therapeutic dilemma (Review)

Abstract: Sarcoidosis, a chronic, inflammatory disease that affects various different organs, is characterized by noncaseating epitheloid granulomas. This systemic inflammatory process is associated with an increased risk of cancer. Several cases of sarcoidosis that mimic metastatic tumor progression in radiological findings have been reported so far. However, there are also cases that have presented a coexistence of sarcoidosis and metastasis, which have caused a diagnostic and therapeutic dilemma. Due to inadequate cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 62 publications
4
31
0
1
Order By: Relevance
“…Moreover, there are cases like ours in which sarcoidosis and malignant diseases coexist, leading to diagnostic dilemmas. 7,8 Paparel et al reviewed 64 cases in which sarcoidosis coexisted in patients with testicular cancer. 7 Seminoma was the most common histological type of testicular cancer among these patients (63%, 40/64).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are cases like ours in which sarcoidosis and malignant diseases coexist, leading to diagnostic dilemmas. 7,8 Paparel et al reviewed 64 cases in which sarcoidosis coexisted in patients with testicular cancer. 7 Seminoma was the most common histological type of testicular cancer among these patients (63%, 40/64).…”
Section: Discussionmentioning
confidence: 99%
“…72 There are numerous studies that also report an association between sarcoidosis and other solid-organ cancers, but breast cancer is the most commonly observed and accounts for 20 to 21% of cases. 72,73 Other malignancies commonly reported to occur with sarcoidosis include melanoma, cervical, and thyroid cancer. 72,73 Just less than 5% of sarcoidosis patients from a prospective cohort were identified to have cancer that occurred preceding, concurrently, or subsequent to sarcoidosis; however, the risk of subsequent cancer in patients with known sarcoidosis is debated.…”
Section: Sarcoidosis and Malignancy Overviewmentioning
confidence: 99%
“…72,73 Other malignancies commonly reported to occur with sarcoidosis include melanoma, cervical, and thyroid cancer. 72,73 Just less than 5% of sarcoidosis patients from a prospective cohort were identified to have cancer that occurred preceding, concurrently, or subsequent to sarcoidosis; however, the risk of subsequent cancer in patients with known sarcoidosis is debated. 74 A large registry study from Sweden and Denmark found sarcoidosis patients were more likely to develop high-grade non-Hodgkin's lymphoma (NHL) than those without a history of sarcoidosis.…”
Section: Sarcoidosis and Malignancy Overviewmentioning
confidence: 99%
“…First line treatment of sarcoidosis is corticosteroids with antimetabolites generally used when unresponsive to steroids [1]. Granulomatous inflammation can rarely be seen in lung cancer tumors and regional draining lymph nodes which is called 'sarcoid like reaction' as they do not fulfill the criteria for systemic sarcoidosis [2]. Sarcoid like reaction can coexist with malignancy either at the time of diagnosis or later during follow up after treatment or from oncologic immunotherapy [2,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Granulomatous inflammation can rarely be seen in lung cancer tumors and regional draining lymph nodes which is called 'sarcoid like reaction' as they do not fulfill the criteria for systemic sarcoidosis [2]. Sarcoid like reaction can coexist with malignancy either at the time of diagnosis or later during follow up after treatment or from oncologic immunotherapy [2,10,14]. It can be challenging at times in such cases when tissue biopsies only pick up sarcoid changes without revealing malignancy because of sampling areas in that particular tumor and further delaying the actual diagnosis which happened in our case.…”
Section: Introductionmentioning
confidence: 99%